2021
DOI: 10.1111/ced.14884
|View full text |Cite
|
Sign up to set email alerts
|

Equal rates of drug resistance in leprosy cases with relapse and recurrent/chronic Type 2 reaction: time to revise the guidelines for drug‐resistance testing in leprosy?

Abstract: Background. Leprosy relapse/recurrence is a serious concern particularly in a leprosy-endemic nation such as India. It is believed that bacilli persisting even after multidrug therapy can cause relapse; recently, however, drug resistance as a cause for recurrences and chronic erythema nodosum leprosum (ENL) has been speculated. Aim. To study drug-resistance patterns in cases of leprosy relapse and chronic/ recurrent (c/r)ENL. Methods. This cross-sectional study conducted over a period of 1 year included patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Resistance to rifampicin and dapsone was reported in 8.3% and 12.5% of patients with recurrent/chronic ENL respectively, in a recent study from a tertiary care institute in North India. [ 3 ] Five of the six cases with chronic ENL in the present study had resistance to one or more drugs, with two having rifampicin resistance. Modification of treatment regimens in both resulted in excellent control of their type 2 reaction.…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…Resistance to rifampicin and dapsone was reported in 8.3% and 12.5% of patients with recurrent/chronic ENL respectively, in a recent study from a tertiary care institute in North India. [ 3 ] Five of the six cases with chronic ENL in the present study had resistance to one or more drugs, with two having rifampicin resistance. Modification of treatment regimens in both resulted in excellent control of their type 2 reaction.…”
mentioning
confidence: 78%
“…[ 2 ] However, a recent study has suggested modifying these criteria to include those presenting with chronic/recurrent erythema nodosum leprosum (ENL) as well. [ 3 ]…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence and 95% CI of the drug−resistance rate for each study are represented. Forest plot of drug−resistance rates of Mycobacterium leprae isolates in studies meeting inclusion criteria (n = 25) [ 14 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Figurementioning
confidence: 99%
“…( a ) The forest plot of the Ser mutation in RpoB. ( b ) The forest plot of the Pro mutation in Folp1 [ 14 , 20 , 21 , 24 , 25 , 27 , 28 , 29 , 30 , 31 , 32 , 34 , 35 , 37 , 38 ].…”
Section: Figurementioning
confidence: 99%